A Functionality Testing Method Based on Exploratory Testing for Android Mobile Apps. Issue 1 (April 2021) - Yu, Jiujiu; Zhang, Jishan; Wu, Ning; Mei, Yingying; Zhang, Deqing; Zhu, Lili; Zhu, Canglu; Zhu, Shaomin
Abstract: The research is based on the characteristics of mobile Applications (Apps), taking an Android mobile App of a small examination system as an application case, this study is devoted to exploring a feasible functionality testing method based on exploratory testing for Android mobile Apps, which includes fundamental functionality logic verification, Graphical User Interface (GUI) automated testing, and special testing. Furthermore, further work is put forward to apply this functionality testing method to IOS mobile Apps, adding new test items for mobile Apps and improving the method of depth-first search for control traversal in GUI automated testing.